Avaliação em educação física escolar no contexto do ensino inclusivo - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2013)
This study treats has the objective to revel the ideological assumptions what subsidize the pedagogic practices in Scholar Physical Education, in the schools of states system and municipal system of education in Itararé-SP town, face to challenges of scholar inclusion process. For this was collected Politic Project of Schools and Teaching Plans of Scholar Physical Education Teachers. For to identify the ideological tendency inserted in this documents was used the technical of Content Analysis and the vision of Discourse Analysis, what sought to highlight the statements about evaluation, inclusion and Physical Education. This is a qualitative research and consist in a documentary analyze. The object of study is the expression of elements above (evaluation, inclusion and Physical Education) associated at terms and adjectives used in such documents, trying to identify the meanings and senses assigned to this and what ideology those terms are connected. With such study, was possible to revel too, if the ideological tendency favors or not, the inclusion process of students with deficiency at regular school. The theoretical reference was the laws related by education and inclusion, and the documents what are basement for scholar pedagogic practices in Scholar Physical Education, from levels national, states until specify by each school, and some authors who discourses about inclusion, about evaluation and Physical Education what corroborate with the conception of education, man and society of this researcher. The result is the interpretation of the neoliberal ideology has a deep influence in a big part of what do and how do the educational process in those schools, and the Physical Education in this case, has following the same flux, and independent the inclusive process has advanced last years, has still obstacles in a attitudinal order to be realized in fact.
Evaluation on school physical education in the context of inclusive education
Keywords: inclusão; educação física escolar; avaliação; inclusion; scholar physical education; evaluation; CNPQ::CIENCIAS HUMANAS::EDUCACAO